O estudo da dependência da polarização e do deslocamento Raman no espalhamento Stokes e anti-Stokes correlacionado no diamante - Diego Sier de Faria (2024)
The present dissertation entails a detailed investigation into the asymmetry in the formation of correlated Stokes and anti-Stokes photon pairs before and after the resonance region in a diamond sample. The analysis undertaken in this study is based on the dependence on polarization and frequency, combined with two distinct crystallographic orientations of the sample, aiming to explore the physical characteristics of this asymmetry. Initially, the physical and structural properties of diamond are presented. Subsequently, the physical phenomenon under study is addressed, starting from uncorrelated Raman scattering to correlated Raman scattering. Following this, the experimental apparatus used to measure the desired physical quantities is described. The results obtained are then discussed. Finally, the conclusion section provides a concise and general analysis of the experimental results, which indicate that correlated Stokes and anti-Stokes Raman scattering constitutes a specific type of four-wave mixing. This four-wave mixing can be divided into a resonant part and a non-resonant part, providing an adequate explanation for the asymmetry issue.